2006
DOI: 10.1080/07391102.2006.10507106
|View full text |Cite
|
Sign up to set email alerts
|

Complex Inhibition of Tyrosinase by Thiol-Composed Cu2+Chelators: A Clue for Designing Whitening Agents

Abstract: The inhibition of tyrosinase has attracted considerable attention for potential medicinal and cosmetic applications, as well as in agriculture. This study investigated the inhibition effects of thiol-associated Cu(2+) chelators and deduced a strategy for designing and/or selecting tyrosinase inhibitors. Among the several compounds tested, dithioglycerine (DTGC) was selected for further experiments on the inhibition kinetics on tyrosinase. Different types of tyrosinases derived from mushroom and from the transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
20
1
1
Order By: Relevance
“…The partial conformational changes induced by TFE are likely to have affected the substrate-enzyme state of the parabolic V max changes and, simultaneously, interfered with L-DOPA docking to the active site, resulting in K m changes. Complex types of inhibition of tyrosinase by various compounds have been observed previously [25,26,[33][34][35]. Compared to these results, however, the TFE-induced mechanism of inhibition was different in two major ways: TFE did not bind directly to the copper ions of the active site, and secondary structural changes were accompanied by tertiary structural changes that directly induced a complete loss of activity.…”
Section: Discussioncontrasting
confidence: 51%
“…The partial conformational changes induced by TFE are likely to have affected the substrate-enzyme state of the parabolic V max changes and, simultaneously, interfered with L-DOPA docking to the active site, resulting in K m changes. Complex types of inhibition of tyrosinase by various compounds have been observed previously [25,26,[33][34][35]. Compared to these results, however, the TFE-induced mechanism of inhibition was different in two major ways: TFE did not bind directly to the copper ions of the active site, and secondary structural changes were accompanied by tertiary structural changes that directly induced a complete loss of activity.…”
Section: Discussioncontrasting
confidence: 51%
“…Certain compounds having thiols, such as ESH, are known to be powerful nucleophiles that can chelate Zn 2+ and Cu 2+ (Park, Lyou, Hahn, Hahn, & Yang, 2006). Furthermore, Hanlon (1971) reported that, of the 4 copper enzyme systems under study, only PPO was inhibited by ESH.…”
Section: Discussionmentioning
confidence: 97%
“…In vitro experiments clearly showed that exogenous L-ESH decreased crab HLS PO activity. Certain compounds having thiol, such as ESH, are known to be powerful nucleophiles that can chelate Zn 2+ and Cu 2+ (Hanlon, 1971;Park, Lyou, Hahn, Hahn, & Yang, 2006). It has been known that PO and hemocyanin from crustaceans have oxygen-binding sites that are formed by two copper ions (Kim et al, 2002).…”
Section: Discussionmentioning
confidence: 98%